(untitled) (Indian Journal of Nematology, 2024)
: The comparative efficacy of formulated products of Purpureocillium lilacinum (PL), Trichoderma harzianum (TH), Pseudomonas fluorescens (PF), Pochonia chlamydosporia (PC), and neem cake (as an organic amendment) against Meloidogyne incognita infecting bitter gourd was evaluated at Central Research Farm, Nadia, West Bengal (India) for three years. The experimental findings from the first year showed that PL+Farm yard Manure (FYM), PF, and PL alone were the most effective bioproducts for managing rootknot nematodes in bitter gourd. Again, in the second and third years, PL+FYM showed effectiveness in reducing soil nematode population, nematode infestation, and improving fruit yield in bitter gourd. After pooling the data from three seasons, it was clear that PL+FYM was the best to increase vine length, lower the number of soil nematodes (56.81%) and nematode infestations (RKI 2.58%), and obtain a higher fruit yield (85.63%) (9.40 t/ha). The incremental cost-benefit ratio (ICBR) calculated for PL+FYM was 1:3, which was considered quite favourable for the growers. However, the greater return was fetched from the carbofuran treatment (ICBR 1:14). The present study demonstrated that the application of P. lilacinum along with FYM could be effective and economical in controlling root-knot nematodes under field conditions. Further, the level of efficacy of bioproducts against rootknot nematode on bitter gourd was not comparable with soil application of carbofuran. This study revealed neem cake (30 g/pit) and P.fluorescens (10 g/pit) are two effective and economical alternatives, but TH and PC are not effective in reducing the soil population of M. incognita.